2016
DOI: 10.1111/dom.12662
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of self‐monitoring of blood glucose in insulin‐treated diabetes: analysis of a Scottish population over time

Abstract: Analysis of a diabetes clinical information system in Tayside, Scotland, shows that a significant proportion of insulin-treated patients with diabetes are not self-monitoring blood glucose according to current clinical guidance and recommendations, with some not self-monitoring their blood glucose at all. Although there has been an increase in the numbers of reagent strips dispensed over the past decade, this increase is mainly accounted for by increased testing frequency among people with diabetes already tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…These people are usually less motivated or more reluctant of using the often‐considered hassle and inconvenient conventional BGM. A population‐based study even lately indicated that up to 1‐third of individuals with type 1 diabetes do perform no BGM at all . Our study conducted in real‐life conditions therefore suggests that the access to the FGM technology tends to improve the willingness of individuals with poor glycaemic control to better take care of the disease.…”
Section: Discussionmentioning
confidence: 75%
“…These people are usually less motivated or more reluctant of using the often‐considered hassle and inconvenient conventional BGM. A population‐based study even lately indicated that up to 1‐third of individuals with type 1 diabetes do perform no BGM at all . Our study conducted in real‐life conditions therefore suggests that the access to the FGM technology tends to improve the willingness of individuals with poor glycaemic control to better take care of the disease.…”
Section: Discussionmentioning
confidence: 75%
“…Recent population-based data indicate that day-to-day blood glucose testing frequency is low, with a mean number of test strips dispensed per day of 1.5 for insulin-treated Type 2 diabetes and 2.6 for Type 1 diabetes, with around one-third of individuals with Type 1 diabetes probably not testing at all [12]. These results support findings that up to 60% of drivers with diabetes never test their glucose level before driving and this low testing frequency has changed little in the last decade [5,6,13,14].…”
Section: What's New?mentioning
confidence: 99%
“…2 Despite growing evidence on the importance of SMBG as a key component of self-management, many people who are recommended to test routinely are not testing as frequently as recommended, and many are not testing at all. 3 There is also wide variation in individual practice of SMBG: frequency, timing, the measurement itself, interpretation of readings, resulting actions taken, and evaluation of the outcome. 4 These wide variations in practice may account for why clinical benefits identified from experimental studies that require SMBG to be undertaken according to strict protocols are often not replicated in observational studies.…”
Section: Introductionmentioning
confidence: 99%